Analisis Penyebaran Temperatur pada Desain Mold Prototype Mesin Injeksi Molding Manual Double Barrel Kapasitas 5 TF - Prawira, Valen Yudha; Muslimin; Silitonga, Muhammad Prasha Risfi; Almahdi (Jurnal Poli-Teknologi, 2024)
This study analyzes the temperature spread distribution in the core and cavity design of a manualdouble-stage injection molding machine with a 5 tons force (TF) capacity. The injection mold isutilized to process polypropylene (PP) material into an injection product in the shape of the PNJlogo. This research aims to examine the temperature spread distribution resulting from a 100-wattcartridge heater located on the support plate of the mold, with a focus on the core and cavitytemperatures. Manual calculations using heat transfer conduction principles and finite elementanalysis (FEA) simulations using software were conducted in this study. The parametersinvestigated include the temperature values across the support plate mold, core, and cavity. Theresults of the manual calculations indicate that the temperatures on the support plate mold, core,and cavity are 58.96°C, 57.34°C, and 57.34°C, respectively. The simulation analysis yieldedmaximum temperatures of 89.53°C for the support plate mold and 88.11°C for both the core andcavity. The manual calculations and simulation analysis produced accurate and reliable results,confirming that the standard mold temperature range for processing polypropylene is between20°C and 90°C. This analysis demonstrates that the identified temperature levels are safe forpolypropylene processing, providing high confidence in the validity of the research findings.